(untitled) (Conferencea, 2023)
This article investigates the factors that influence the financial stability of local budgets. The study uses theoretical and methodological approaches to analyze the composition and dynamics of state budget expenditures, as well as the relationship between state and local budget expenditures. The article provides practical recommendations for optimizing the expenditure structure to ensure financial stability of local budgets.